Blockchain adoption in the maritime industry - Pu, Shuyi (Nanyang Technological University, 2022)
Blockchain has become one of the emerging technologies set to disrupt the maritime industry. Increasingly, maritime logistics and services providers are looking to adopt the technology to stay ahead of competition. However, studies on blockchain adoption in the maritime sector have been scarce. Therefore, this research aims to narrow the literature gap by analysing blockchain adoption in the maritime industry deeply and solving related practical adoption questions quantitatively. This research starts with a systematic analysis of current blockchain applications in various sectors of the maritime industry. A novel conceptual framework is also developed to provide a holistic view of how blockchain technology can be applied in the maritime industry and guide future research. Then, this research focuses on three practical problems regarding blockchain adoption in the maritime industry, namely optimal adoption time, evolution of adoption and greenhouse gas impact. Firstly, a game theoretic model is built to analyse companies’ optimal adoption time of blockchain when facing a request of a big customer, which is an emerging trend in the industry. A big shipper and multiple ship operators are used as a case in the study. Secondly, an asymmetric evolutionary game model is built to examine the potential evolution of blockchain adoption rate in multi-agent systems, using blockchain electronic bills of lading as an example. Thirdly, an estimation framework with concrete methods is developed to estimate the national greenhouse gas impact of blockchain for digitalising shipping documents. Taking Singapore and China as examples, the difference in greenhouse gas performance between blockchain and centralised systems is also compared in the study. This research makes several contributions. It deepens the literature by analysing blockchain adoption in the maritime industry in a holistic view. It makes novel attempts to solve practical problems of blockchain adoption in a quantitative way, including adoption time, evolution of adoption rate and environmental impact. It pushes the boundary of relevant literature from qualitative studies to more quantitative analysis. Meanwhile, it provides useful decision tools and insights to maritime stakeholders on policies and business strategies to foster and accelerate blockchain adoption in the industry.